A cascade synthetic route to new bioactive spiroindolinepyrido[1, 2-a]indolediones from indirubin. Issue 43 (28th October 2015) - Sele, Alexander M.; Bremner, John B.; Willis, Anthony C.; Haritakun, Rachada; Griffith, Renate; Keller, Paul A.
Abstract: The allylation of indirubin produced the expected indolic N ′-allylindirubin and N, N ′-diallylindirubin derivatives in moderate yields, together with the corresponding N -substituted isatin products. At higher temperatures, the base-initiated reaction with allylic halides yielded spiroindolinepyrido[1, 2- a ]indolediones in a one-pot cascade reaction sequence with yields of up to 70%. These readily accessed, new spiro compounds represent the first reported examples of indirubin participating in cascade reactions. Preliminary in vitro biological testing of some of the products indicated promising activity against some cancer cell lines and against Plasmodium falciparum for two spiro derivatives. Computational methods were used to gain a greater understanding of the UV/Vis spectroscopic data for the N ′-substituted and N, N ′-disubstituted indirubin derivatives. Graphical abstract: